2021
DOI: 10.17557/tjfc.1033784
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interaction and Stability Analysis for High Yielding Doubled Haploid Lines of Lowland Rice

Abstract: This study was aimed at obtaining information on the effects of G × E interaction on yield among doubled haploid lines (DH) of lowland rice and to obtain stable and high yielding lines. The experiment was conducted in 9 environments (E),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The stability analysis stated by Finlay and Wilkinson (1963) determines stable hybrids by considering the slope of the regression line or regression coefficient (bi) and the hybrids' mean yield at the overall location. Akbar et al (2021) state that bi-value differences indicate hybrid responses to environmental changes. A stable hybrid is shown by a hybrid with bi-values not significantly different from 1, a hybrid with above-average stability (suitable for sub-optimal environments conditions) has bi-values less than 1, and a hybrid with below-average stability (suitable for optimal environments conditions) has bi-values more than 1 (Kartina et al, 2019;Shojaei et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The stability analysis stated by Finlay and Wilkinson (1963) determines stable hybrids by considering the slope of the regression line or regression coefficient (bi) and the hybrids' mean yield at the overall location. Akbar et al (2021) state that bi-value differences indicate hybrid responses to environmental changes. A stable hybrid is shown by a hybrid with bi-values not significantly different from 1, a hybrid with above-average stability (suitable for sub-optimal environments conditions) has bi-values less than 1, and a hybrid with below-average stability (suitable for optimal environments conditions) has bi-values more than 1 (Kartina et al, 2019;Shojaei et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Stability analysis based on Finlay-Wilkinson and Eberhart-Russell methods effectively described the genotype's responses in various environments [61][62][63]. However, these two methods were unable to explain the overall impact of various locations and seasons on plant yields [53].…”
Section: Stability Criterion Of Genotypes Based On the Three Stabilit...mentioning
confidence: 99%
“…Anshori et al (2022) suggested that DH technology could accelerate the release of new varieties of rice. Several elite lines have been obtained from the results of DH development including 28 black rice lines with good agronomic characters (Alsabah et al 2019), 15 DH rice lines that are tolerant to salinity stress (Anshori et al 2022), 2 lines superior rice widely adaptable in all locations (Akbar et al 2021a), 9 lines DH that have the best performance based on the character of grain yield, number of grain content per panicle, percentage of grain content, and panicle length (Chitanda et al 2022), rice being injected with genes for resistance to blast and bacterial leaf blight (Chauhan et al 2021), 4 varieties of hybrid rice (Sharma et al 2021), and 129 DH plants from biparental crosses (Tripathy 2022).…”
Section: Introductionmentioning
confidence: 99%